Uterine lipo-leiomyoma in post-menopausal women: two interesting cases - Shenoy, Heera Trivikrama; Kambalavan, Shibin; Puthuprakkat, Shameema; Singh, Mary Nandini; Sasidharan, Athira; Thomas, Jomy Perumcheril (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Lipo-leiomyomas (LL), incidentally found lipomatous variants of uterine leiomyomas do not require surgical intervention unless symptomatic. Large LL of the uterine body is very rare. Majority being benign, these could co-exist with other gynaecological malignancies, metabolic diseases and abnormal oestrogen statuses and do rarely transform to liposarcoma. Here, we presented two interesting cases of postmenopausal women with LL. Ultrasonography and MRI performed in the workup of both, incidentally demonstrated a fatty lesion arising from the uterine corpus, consistent with a lipo-leiomyoma. This case report stresses the need for greater awareness of these variants regarding histogenesis, diagnosis and treatment.